Specifics of Al substitution into boron carbide: A DFT study - Oleksandr Vasiliev; Vladyslav Bilyi (Open Ceramics)
Boron carbide (B4C), known for its hardness and low density, is prone to local amorphization under high non-hydrostatic loads, limiting its applications. Aluminum doping is promising due to aluminum's atomic size, fitting into the B4C crystal lattice, particularly the intericosahedra chain, potentially reducing amorphization. This work uses first-principles calculations to study aluminum placement in B4C. We examine the potential for Al substitution in the icosahedron and intericosahedra chain, identifying possible locations. Results show that aluminum can't replace atoms in the icosahedron, but substituting one central atom in the intericosahedra chain with aluminum is energetically favorable and likely changes the chain configuration to an angular one. Additionally, aluminum can substitute one carbon in the (C-B-C) chain of B12(C-B-C) boron carbide. Comparative analysis suggests these configurations may coexist. Our study offers a theoretical model that can guide future experimental efforts and provides valuable insights into the structural specifics of aluminum-doped boron carbide.